2012
DOI: 10.1088/0953-8984/25/4/045001
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of size calibrated three-dimensional nanodots in atomistic model of strained epitaxy: a Monte Carlo study

Abstract: We introduce a simple model of strained epitaxy to study the growth of coherent several-monolayers-high nanoislands at low coverage. The size mismatch between the substrate (which is assumed to be rigid and passive) and the growing overlayer is modelled by the hard-sphere interaction between the adatoms. In the case of positive misfit the sphere diameter is larger than the substrate lattice parameter. Elastic interactions are described within the harmonic approximation to the substrate potential in the vicinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…This is reasonable because the adatoms nucleate an island when meeting at one spatial point in the continuum approximation (or at the nearest sites on the lattice) while according to (44) and (45) the adatom at point x nucleates an island with any other adatom in the system which is unphysical. Secondly, in (44) the nucleation term enters with the coefficient 2, in contrast to our equation (43). The origin of this discrepancy is connected with the last term of (44) that is absent in our equation (43) but is present as the last term in (42)).…”
Section: Comparison With Equations From the Self-consistent Approach mentioning
confidence: 76%
See 1 more Smart Citation
“…This is reasonable because the adatoms nucleate an island when meeting at one spatial point in the continuum approximation (or at the nearest sites on the lattice) while according to (44) and (45) the adatom at point x nucleates an island with any other adatom in the system which is unphysical. Secondly, in (44) the nucleation term enters with the coefficient 2, in contrast to our equation (43). The origin of this discrepancy is connected with the last term of (44) that is absent in our equation (43) but is present as the last term in (42)).…”
Section: Comparison With Equations From the Self-consistent Approach mentioning
confidence: 76%
“…As we showed in the present paper, even in the simplest case of the irreversible submonolayer growth in precoalescence regime that has been extensively investigated for about forty years there still remain controversial issues that need further investigation. Obviously that in more complex cases such as the currently hot subject of the quantum dot growth [42,43] the difficulties will enlarge manifold. We expect that the formalism developed in the present paper will prove to be an indispensable tool of derivation of the REs for such cases.…”
Section: Resultsmentioning
confidence: 99%
“…Hereafter, the growth behavior with a growth exponent β > 1/2 is called "superepitaxial growth behavior." In the conventional kinetic theory, QDs are generally considered to grow via uphill mass transport of adatoms driven by the latticemismatch strain [189], which can be implemented well in KMC simulations [190][191][192][193][194]. In their KMC simulation of the heteroepitaxial growth (with the elastic property of the system similar to semiconductors) at a lattice mismatch of 5%, Ratsch et al [192] observed the formation of 3D islands that grow according to the super-epitaxial growth law…”
Section: Super-epitaxial Growthmentioning
confidence: 99%
“…Another simplification is to neglect the displacements of the surface atoms in the direction perpendicular to the surface, as suggested in [3,4,31]. This leaves us with onedimensional (1D) chains of atoms lying at the rigid substrate [30,11]. Their relaxation can be described within the harmonic Frenkel-Kontorova model as follows [30].…”
Section: The Model Of Strained Islandsmentioning
confidence: 99%